2020
DOI: 10.1038/s41467-020-16076-0
|View full text |Cite
|
Sign up to set email alerts
|

Mode-resolved reciprocal space mapping of electron-phonon interaction in the Weyl semimetal candidate Td-WTe2

Abstract: The excitation of coherent phonons provides unique capabilities to control fundamental properties of quantum materials on ultrafast time scales. Recently, it was predicted that a topologically protected Weyl semimetal phase in the transition metal dichalcogenide Td-WTe2 can be controlled and, ultimately, be destroyed upon the coherent excitation of an interlayer shear mode. By monitoring electronic structure changes with femtosecond resolution, we provide here direct experimental evidence that the shear mode a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 43 publications
5
40
1
Order By: Relevance
“…7 and Supplementary Fig. 8 , we show that when the photon energy is 1.5 eV, the interlayer movement always starts from the T d phase to the centrosymmetric phase, which is consistent with experimental observations 37 , 42 , 43 . To show the distinct evolution of WPs separation, the phase diagram as functions of photon energy and incident direction is constructed, as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…7 and Supplementary Fig. 8 , we show that when the photon energy is 1.5 eV, the interlayer movement always starts from the T d phase to the centrosymmetric phase, which is consistent with experimental observations 37 , 42 , 43 . To show the distinct evolution of WPs separation, the phase diagram as functions of photon energy and incident direction is constructed, as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…In Supplementary Fig. 2 , we show that consistent with the experiment observation, optical phonon modes at the frequency of ~4 THz are of particular relevance in the early stages of the phase transition 43 . A representative mode that belongs to the group of m -modes is shown in Supplementary Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Recent experimental advances in time-and angularresolved photoelectron spectroscopy (TR-ARPES), however, have shown that a more direct observation of electron phonon coupling is possible [19,20]. These works show that with sufficiently clean data it is possible to extract some electron-phonon coupling properties by Fourier analysis of TR-ARPES data, in a method called frequency-domain ARPES (FD-ARPES) by some authors [20].…”
mentioning
confidence: 99%